2015
DOI: 10.3201/eid2102.131610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Border Entry Screening for Infectious Diseases in Humans

Abstract: Outbreak-associated communications for travelers and clinicians may be a more effective approach to the international control of communicable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…This allows the viruses to rapidly spread across continents, and efforts at airport screening to halt them have been fairly ineffective and costly. 5,6 This is in addition to the potential for in-flight transmission of the virus among passengers that was observed with SARS. 7 Once the pathogen has landed in a new country, the likelihood of contagion and spread is dependent on local transmission pathways and the strength of local health protection systems.…”
Section: Editorialmentioning
confidence: 99%
“…This allows the viruses to rapidly spread across continents, and efforts at airport screening to halt them have been fairly ineffective and costly. 5,6 This is in addition to the potential for in-flight transmission of the virus among passengers that was observed with SARS. 7 Once the pathogen has landed in a new country, the likelihood of contagion and spread is dependent on local transmission pathways and the strength of local health protection systems.…”
Section: Editorialmentioning
confidence: 99%
“…For example, the value of entry screening measures has been questioned, 9,10 while an evaluation of border entry screening measures in several countries concluded that a combination of communication methods (eg, in the form of pre-flight health information, in-flight videos, and clinical guidance) for passengers and clinicians might be a more effective strategy for global infectious disease control. 11 Collectively, the unique dynamics and interactions at play in an aircraft environment require a distinct response to infectious disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Upon arrival, travellers may be asymptomatic, either in the incubation period or have a subclinical infection, have mild symptoms, use antipyretics to reduce fever, or may not report their symptoms. Because cases may be missed, entry screening has been described as ineffective and resource-intensive (13,(20)(21)(22). However, the efficacy of border screening is difficult to evaluate (23).…”
Section: Discussionmentioning
confidence: 99%